Effect of grain structure on fatigue crack propagation behavior of Al-Cu-Li alloys. (10th June 2023) - Lu, Dingding; Lin, Ben; Liu, Tianle; Deng, Sanxi; Guo, Youjie; Li, Jinfeng; Liu, Danyang
Highlights: The microstructure evolutions and fatigue crack propagation behaviors of Al-Cu-Li alloys with hot-rolled and cold-rolled were firstly investigated by FCP tests. The mechanisms of subgrain boundaries within grains on the crack initiation and propagation have been discussed. The relationship between crystal orientation and crack path deflection and its influences on the fatigue crack propagation has been discussed in detail. Direct experiments were carried out to prove the retardation of crack propagation by grain boundaries and deflection. Abstract: Recrystallization behavior during optimized heat treatments provides a potential to obtain desirable grain structure, which significantly improves the mechanical properties of aluminum alloys. The influence of grain structures on fatigue crack propagation (FCP) behaviors of Al-Cu-Li alloy with hot-rolled (HR) and cold-rolled (CR) was investigated. Subgrain boundaries have a significant impact on small crack growth rates, which is reflected in the pronounced fluctuation of fatigue crack growth of HR specimens after solution treatment. Moreover, the specific cellular structure within grains can improve the deformation capacity of alloys due to their accommodation of plastic deformation, which contributes to the lower fatigue crack growth rates and higher threshold values in HR specimens. The intragranular deflection also decelerates the FCP rate and occurs in these regions of large grain without subgrain boundaries. Recrystallization occurs in the CR specimens, resulting in small anisotropy on the fatigue resistance for the different orientations in the Paris stage due to the recrystallization texture. Fatigue cracks can be deflected and tend to propagate along the grain boundaries when it goes into the grain with a relatively low Schmidt factor value. Graphical abstract: Image, graphical abstract